DAMPAK KEBIJAKAN INJOURNEY TOURISM DEVELOPMENT CORPORATION TERHADAP KETERLIBATAN MASYARAKAT LOKAL DALAM PARIWISATA BERKELANJUTAN DI MANDALIKA LOMBOK - Sri Rizki A.K, Rieke; Azhar, Rai Thoriq; Arum Fathanah, Nalya; Devinta, Melani (JURNAL MEKAR, 2025)
The aim of this research is to determine the extent to which the InJourney Tourism Development Corporation (ITDC) policy contributes to encouraging local community involvement in tourism destinations, especially in the Mandalika Lombok area. Local community participation in sustainable tourism is greatly influenced by the policies implemented by ITDC. This research uses descriptive qualitative research methods and uses secondary data sources. It is known that ITDC policies have given the community access to new economic opportunities through empowerment and training programs. On the other hand, there are also difficulties that arise, such as limited community participation in strategic decision making and limited access to information and decisions related to tourism development. This research highlights the importance of changing legislation to make it more inclusive to maximize local community involvement, which in turn will promote the sustainability of the region’s tourism industry